High-temperature high-strength ceramic wear-resistant castable as well as preparation method and construction method thereof

By using submicron SiO2 powder, activated alumina powder and rare earth modified titanium aluminum steel fibers in high-temperature high-strength ceramic wear-resistant castables, combined with brown corundum and sintered mullite aggregates, the problem of degradation of traditional materials at high temperatures is solved, and the effect of high-temperature high-strength wear-resistant performance and reducing maintenance costs is achieved.

CN119591385AActive Publication Date: 2025-03-11WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD

Patent Information

Application Number
CN202411644340.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Traditional high-strength wear-resistant castables at high temperatures are caused by low melts in cement CaO and aggregate, which leads to a significant reduction in wear resistance and the risk of long baking time and prone to bursting.

Method used

Submicron SiO2 powder is used as a binding agent, combined with activated alumina powder and rare earth modified titanium aluminum steel fibers, and brown corundum and sintered mullite are used as aggregates to generate interlaced mullite phases through in-situ sintering reactions to form a high-temperature, high-strength wear-resistant castable.

Benefits of technology

It improves the high-temperature flexural strength, compressive strength and thermal shock resistance of the material, solves the problem of degradation of traditional materials at high temperatures, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139309480000091
    Figure BDA0005139309480000091
  • Figure BDA0005139309480000101
    Figure BDA0005139309480000101
Patent Text Reader

Abstract

The invention belongs to the technical field of refractory materials, and discloses a high-temperature high-strength ceramic wear-resistant castable as well as a preparation method and a construction method thereof. The high-temperature high-strength ceramic wear-resistant castable is prepared from the following raw materials in percentage by mass: 14 to 22 percent of mullite with the particle size of 8 to 5mm, 16 to 24 percent of mullite with the particle size of 5 to 3mm, 13 to 18 percent of brown aluminum oxide with the particle size of 3 to 1mm, 12 to 19 percent of brown aluminum oxide with the particle size of 1 to 0.074 mm, 16 to 25 percent of brown aluminum oxide with the particle size of less than or equal to 0.074 mm, 3 to 7 percent of activated aluminum oxide powder, 4 to 7 percent of submicron SiO2 powder and 0.3 to 0.6 percent of pure calcium aluminate cement, and rare earth modified titanium-aluminum alloy fibers accounting for 1-1.5% of the total mass of the raw materials, a water reducing agent accounting for 0.05-0.15% of the total mass of the raw materials, explosion-proof fibers accounting for 0.03-0.1% of the total mass of the raw materials and water accounting for 3.5-4.5% of the The submicron SiO2 powder is used as a binding agent to endow the castable with certain normal-temperature strength, the activated alumina powder is combined to provide high-temperature strength, the brown fused alumina and the sintered mullite are used as aggregates, and the rare earth modified titanium aluminum steel fibers are combined to endow the castable with high-temperature, high-strength and wear-resistant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a high-temperature and high-strength ceramic wear-resistant castable and a preparation method and a construction method thereof. Background Art

[0002] In high-temperature industries, mechanical impact, wear, and thermal stress damage are common forms of damage to industrial furnace lining materials, and maintenance due to wear and tear causes huge economic losses every year. Industrial furnaces such as hot blast furnace forks, slag flushing ditches, granulation towers, cyclone dust collectors, flues, sintering bellows, coke oven brackets, etc., traditionally use various high-chromium, high-manganese and other alloy linings. Wear-resistant materials using alloy linings have good wear resistance, impact resistance, and easy processing, but their acid and alkali corrosion resistance, volume stability, and high temperature resistance are far behind non-metallic materials.

[0003] Wear-resistant materials use inorganic non-metallic materials instead of metal materials, which has obvious advantages. The service life of wear-resistant materials using integral casting castables is 3-5 times that of alloy wear-resistant linings. Although the cost per meter of the two materials is similar, the wear-resistant castable has a longer service life and uses less material, and the overall cost can be reduced by 50-70%. In addition, in the later stage of service, after the wear-resistant lining is severely worn, it only needs to be quickly repaired and maintained by pouring or coating the bottom of the ditch. The maintenance material consumption is small and the cost is very low. The wear-resistant alloy lining needs to be replaced as a whole, and the construction period and cost will be higher. The use of high-strength wear-resistant castables for integral casting of the wear-resistant parts of industrial kilns has a short construction period, low construction difficulty, long service life, and low later maintenance costs. It can save a lot of resources, reduce costs, increase efficiency, and save energy and protect the environment.

[0004] Traditional high-strength wear-resistant castables are made of pure calcium aluminate cement. Due to the presence of CaO in cement, it is easy to form low-melting products such as calcite with Al2O3 and SiO2 in aggregate at high temperatures, which seriously affects the high-temperature performance of the material and greatly reduces the overall wear resistance of the material at high temperatures. At the same time, pure calcium aluminate cement-bonded wear-resistant castables also have the risk of long baking time and easy cracking. Therefore, it is necessary to develop a new type of high-temperature, high-strength wear-resistant castable without cement bonding. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high-temperature and high-strength ceramic wear-resistant castable and a preparation method and a construction method thereof in view of the deficiencies in the prior art. Submicron SiO2 powder is used as a binder to give the castable a certain strength at room temperature, and activated alumina powder is combined to provide high-temperature strength. Brown corundum and sintered mullite are used as aggregates, and rare earth modified titanium aluminum steel fibers are combined to give the castable high-temperature and high-strength wear-resistant properties.

[0006] In order to solve the technical problem proposed by the present invention, the present invention provides a high-temperature and high-strength ceramic wear-resistant castable, comprising the following raw materials in percentage by weight: 14-22% of mullite with a particle size of 8-5mm, 16-24% of mullite with a particle size of 5-3mm, 13-18% of brown corundum with a particle size of 3-1mm, 12-19% of brown corundum with a particle size of 1-0.074mm, 16-25% of brown corundum with a particle size ≤0.074mm, 3-7% of activated alumina powder, 4-7% of submicron SiO2 powder, 0.3-0.6% of pure calcium aluminate cement, and 1-1.5% of the total weight of the above raw materials are added with rare earth modified titanium aluminum alloy fiber, 0.05-0.15% of water reducer, 0.03-0.1% of explosion-proof fiber and 3.5-4.5% of water.

[0007] In the above scheme, the mullite is mullite M60, whose Al2O3 content is 59.5-61.5wt%, SiO2 content is 31.3-33.7wt%, Fe2O3 content is 0.5-1.5wt%, and water absorption rate is ≤0.5%.

[0008] In the above scheme, the brown corundum has an Al2O3 content of 94.5-95.5wt%, a SiO2 content of 0.5-0.8wt%, a Fe2O3 content of 0.01-0.03wt%, a CaO content of 0.2-0.3wt%, a C content of 0.05-0.12wt%, a S content of 0.05-0.08wt%, and a bulk density of ≥3.85g / cm 3 .

[0009] In the above scheme, the Al2O3 content of the activated alumina powder is greater than 99.5wt%, and the median particle size D 50 It is 1.5~1.8μm.

[0010] In the above scheme, the submicron SiO2 powder is obtained by mixing silicon tetrachloride and oxygen in a molar ratio of 1:(6-7), burning at 2400-2450°C for 2-3 hours, and then cooling and solidifying.

[0011] In the above scheme, the submicron SiO2 powder is a spherical amorphous silicon powder, and its particle size is unimodal distribution. 10 0.11~0.15μm, D 50 0.31~0.37μm, D 90 0.79~0.84μm, D 99 It is 0.86~0.92μm.

[0012] In the above scheme, the SiO2 content of the submicron SiO2 powder is 99.93-99.95wt%, the Fe2O3 content is 0.001-0.002wt%, the Al2O3 content is 0.001-0.003wt%, the Na2O content is 0.01-0.02wt%, the K2O content is 0.01-0.02wt%, the SO3 content is 0.01-0.03wt%, and the pH value is 6.8-7.4.

[0013] In the above scheme, the pure calcium aluminate cement is CA70 calcium aluminate cement, with an Al2O3 content of 68.5-71.0wt%, a SiO2 content of 0.6-0.9wt%, a Fe2O3 content of 0.3-0.5wt%, and a CaO content of 29.0-30.5wt%.

[0014] In the above scheme, the rare earth modified titanium aluminum alloy fiber has a length of 40 to 50 mm, a diameter of 0.8 to 1.0 mm, and a softening temperature of 1600 to 1650°C.

[0015] In the above scheme, the preparation method of the rare earth modified titanium aluminum alloy fiber comprises the following steps:

[0016] 1) dissolving a lanthanum source, a cerium source and an ytterbium source in a solvent to obtain a mixed rare earth solution;

[0017] 2) placing the titanium-aluminum alloy fiber into a mixed rare earth solution for vacuum impregnation, taking it out and drying it to obtain a titanium-aluminum alloy fiber after a single treatment;

[0018] 3) uniformly mixing lanthanum chloride, cerium sulfate and ytterbium chloride to obtain a mixed rare earth coating material;

[0019] 4) A mixed rare earth coating material is applied to the surface of the titanium aluminum alloy fiber after the first treatment, and then the fiber is dried and then heated and cured to obtain a rare earth modified titanium aluminum alloy fiber.

[0020] Furthermore, the lanthanum source is one of lanthanum chloride and lanthanum nitrate.

[0021] Furthermore, the cerium source is one of cerium chloride and cerium sulfate.

[0022] Furthermore, the ytterbium source is one of ytterbium nitrate and ytterbium sulfate.

[0023] Furthermore, the solvent is one of NaCl solution, Na2SO4 solution, and NaNO3 solution, and the mass concentration is 30-40%.

[0024] Furthermore, in the mixed rare earth solution, the molar ratio of the lanthanum source, the cerium source and the ytterbium source is (2-2.5):(2-3):1.

[0025] Furthermore, in the mixed rare earth solution, the total mass concentration of the lanthanum source, the cerium source and the ytterbium source is 10-15%.

[0026] Furthermore, the titanium aluminum alloy fiber has an Al content of 46.5-49.0wt%, a Ti content of 47.5-50.0wt%, a Cr content of 1.5-2.0wt%, and a Mn content of 0.3-0.8wt%.

[0027] Furthermore, in step 2), the mass ratio of the titanium aluminum alloy fiber to the mixed rare earth solution during impregnation is 1:(2-3).

[0028] Furthermore, the vacuum degree of the vacuum impregnation is 0.06-0.09 MPa, and the impregnation time is 69-75 hours.

[0029] Furthermore, in step 2), the drying temperature is 105-110° C., and the drying time is 20-24 hours.

[0030] Furthermore, in the mixed rare earth coating material, the mass ratio of lanthanum chloride, cerium sulfate and ytterbium chloride is (2.5-3):(1.5-2):1.

[0031] Furthermore, in step 4), the mass ratio of the titanium-aluminum alloy fiber after the one-time treatment to the mixed rare earth coating material during coating is (9-10):1.

[0032] Furthermore, in step 4), the drying temperature is 105-110° C., and the drying time is 20-24 hours.

[0033] Furthermore, the curing temperature of the heating curing is 350-400° C., the heat preservation time is 3-3.5 hours, and the heating rate is 2-3° C. / min.

[0034] In the above scheme, the water reducer is powdered polyethylene glycol polymer high efficiency water reducer FS20.

[0035] In the above scheme, the explosion-proof fiber is a polypropylene fiber with a length of 3 to 3.5 mm, a diameter of 20 to 30 μm, and a softening temperature of 60 to 70°C.

[0036] In the above scheme, the high temperature and high strength ceramic wear-resistant castable has a 110℃×24h flexural strength ≥12.0MPa, a 110℃×24h compressive strength ≥100.0MPa, a 1100℃×3h flexural strength ≥20.0MPa, a 1100℃×3h compressive strength ≥150.0MPa, a 1550℃×3h flexural strength ≥35.0MPa, a 1550℃×3h compressive strength ≥200.0MPa, a 1400℃×1h high temperature flexural strength ≥15.0MPa, and a wear resistance value of 1500℃×3h ≤2cm3 , the linear change rate after sintering at 1550℃×3h is ≤±0.3%.

[0037] The present invention also provides a method for preparing a high-temperature and high-strength ceramic wear-resistant castable, comprising the following steps:

[0038] Mullite of various particle sizes, brown corundum of various particle sizes, activated alumina powder, submicron SiO2 powder and pure calcium aluminate cement are pre-mixed, and then rare earth modified titanium aluminum alloy fiber, water reducer and explosion-proof fiber are added and stirred and mixed, and finally water is added and stirred to obtain a high-temperature and high-strength ceramic wear-resistant castable.

[0039] In the above scheme, the stirring rate of the stirring is ≥20r / min.

[0040] The present invention also provides a construction method of a high-temperature and high-strength ceramic wear-resistant castable, comprising the following steps:

[0041] The high-temperature and high-strength ceramic wear-resistant material is vibrated into shape and poured as a whole. The material is demoulded after natural hardening, and then wet-cured, baked, and then heated to the working temperature for service.

[0042] In the above scheme, the natural hardening time is 20 to 24 hours.

[0043] In the above scheme, the wet curing time is 72 to 84 hours.

[0044] In the above scheme, the baking is divided into three stages: first, the temperature is raised to 140-160°C and kept for 32-40 hours, then the temperature is raised to 335-375°C and kept for 20-26 hours, and finally the temperature is raised to 620-680°C and kept for 20-26 hours, and the heating rate is 10-12°C / h.

[0045] In the above scheme, after the baking is completed, the temperature is raised to the working temperature at a rate of 30-35°C / h.

[0046] The technical concept of the present invention is as follows:

[0047] 1) Traditional wear-resistant materials are combined with cement, and have high strength at room temperature. However, at high temperatures, CaO in cement forms low-melting products with Al2O3 and SiO2 in the material, which significantly reduces the high-temperature performance. If SiO2 powder is introduced as a binder, there are many impurities, low purity, uneven particle size, and agglomeration. The dispersion is relatively poor, the material curing time is difficult to control, and the material demoulding strength is low. The present invention prepares submicron SiO2 powder by burning silicon tetrachloride and oxygen at a specific temperature. The obtained submicron SiO2 powder has high purity and unique particle size distribution, and the pH value is 6.8-7.4, which is neutral. It is different from the acidic silicon micropowder in producing a slow setting effect on the castable, and it is also different from the alkaline silicon micropowder in producing a accelerating setting effect on the castable, which is easy to control the hardening time of the castable and demoulding treatment. Subsequently, CA70 cement is used as a coagulant and dispersed on the surface and voids of the synthesized submicron SiO2 powder. The CA70 cement hydrate is used as the nucleation point to promote the nucleation, crystallization and crystal growth of Si-O-Si bonds formed by the hydration of the submicron SiO2 powder to form a network structure. Under this synergistic excitation effect, the Si-O-Si bonds of the submicron SiO2 powder continuously form a network three-dimensional chain structure, which can be directly used as a castable binder, so that the material has strength at room temperature, and the demolding flexural strength is ≥3MPa. Under high temperature conditions, the sintering activity and amorphous structure of SiO2 in the submicron SiO2 powder and the Al2O3 in the active alumina powder react through in-situ sintering to generate an interlaced mullite reinforcement phase, further improving the thermal shock stability and high-temperature flexural strength of the material.

[0048] 2) Traditional wear-resistant castables generally enhance the wear resistance of materials by adding steel fibers, but ordinary steel fibers are easy to melt at 1300°C, and the outer dimensions and cross-sectional shape of steel fibers are difficult to control, which is not conducive to the fluidity of castables. The present invention can significantly improve the heat-resistant temperature by rare earth-modified titanium aluminum steel fibers, and still maintain good metal toughness at 1500°C, enhance the toughness, mechanical impact resistance and mechanical strength of the castable, improve the thermal shock resistance of the castable, prevent the microcracks generated in the castable from expanding or extending under the action of thermal stress and mechanical stress, and cause fracture or peeling, and the alloy fiber is easy to bridge and wrap with the castable, which does not affect the fluidity of the castable. The present invention firstly uses vacuum impregnation to infiltrate lanthanum source, cerium source and ytterbium source rare earth into the interior of titanium-aluminum steel fiber to refine its grains. The atomic radius of rare earth elements is larger than that of titanium and aluminum atoms, and the properties are relatively active. The surface defects of the titanium-aluminum alloy phase can be easily filled by vacuum pressure difference impregnation, so that the interfacial tension between the new and old phases is reduced, and the growth rate of the crystal nucleus is increased. At the same time, a surface active film is formed between the grains and the alloy to refine the titanium-aluminum alloy structure. Then, a mixed solution of lanthanum sulfate, cerium nitrate and ytterbium chloride is applied to the surface to form a wrapping protective layer on the alloy surface. The internal structure catalytic toughening and surface wrapping strengthening are jointly modified to synergistically improve the high-temperature performance of the titanium-aluminum steel fiber.

[0049] 3) In the composition design of high-temperature and high-strength ceramic wear-resistant castables, the present invention uses brown corundum and sintered mullite as aggregates. Brown corundum has high strength and rough particle surface; sintered mullite has high purity, good grain development, smooth surface, and good thermal shock stability. Both play the role of network skeleton in the material. Mullite is used to suppress the thermal expansion damage caused by the large thermal expansion coefficient and high elastic modulus of brown corundum, and the impact resistance of mullite is enhanced by brown corundum. The alumina powder and submicron silicon powder added at the same time have high reactivity, which is conducive to the formation of mullite under high temperature reaction without introducing other impurities, thereby improving the purity of the entire material system and the density of the structural network. Through the grading design of mullite and brown corundum, and the close stacking of active powders of different particle sizes, the "arch bridge effect" is formed to greatly improve the strength and wear resistance of the castable.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The present invention synthesizes a submicron SiO2 powder with high purity and unique particle size distribution as a binder, and there is almost no agglomeration phenomenon between its particles, and the pH value is neutral, which will not produce a coagulation-promoting or coagulation-retarding effect on the hardening of the castable, and solves the problem that the submicron silicon powder as a binder has low strength at room temperature and is difficult to demold. In order to achieve the high-temperature and high-strength wear-resistant performance of the submicron SiO2 powder combined with the castable, brown corundum and mullite are selected as aggregates, and the high strength and wear resistance of the brown corundum raw material and the thermal shock resistance stability of mullite are fully utilized, and the high-temperature wear-resistant performance is achieved through a reasonable ratio of brown corundum and mullite; at the same time, the submicron SiO2 powder and the active alumina powder are reacted through an in-situ sintering reaction to generate a staggered distribution of mullite phases, so that the entire material system is a corundum-mullite composite material; in addition, the toughness, mechanical impact resistance and mechanical strength of the castable are further enhanced by rare earth modified titanium aluminum steel fiber, and the high-temperature wear resistance and thermal shock resistance of the castable are improved. DETAILED DESCRIPTION

[0052] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0053] In the following examples, the mullite used is mullite M60, which has an Al2O3 content of 59.5-61.5wt%, a SiO2 content of 31.3-33.7wt%, a Fe2O3 content of 0.5-1.5wt%, and a water absorption rate of ≤0.5%;

[0054] The brown corundum used has an Al2O3 content of 94.5-95.5wt%, a SiO2 content of 0.5-0.8wt%, a Fe2O3 content of 0.01-0.03wt%, a CaO content of 0.2-0.3wt%, a C content of 0.05-0.12wt%, a S content of 0.05-0.08wt%, and a bulk density of ≥3.85g / cm 3 ;

[0055] The Al2O3 content of the activated alumina powder used is greater than 99.5wt%, and the median particle size is D 50 1.5~1.8μm;

[0056] The pure calcium aluminate cement used is CA70 calcium aluminate cement, with an Al2O3 content of 68.5-71.0wt%, a SiO2 content of 0.6-0.9wt%, a Fe2O3 content of 0.3-0.5wt%, and a CaO content of 29.0-30.5wt%;

[0057] The water reducer used is powdered polyethylene glycol polymer high efficiency water reducer FS20;

[0058] The explosion-proof fiber used is polypropylene fiber, with a length of 3-3.5 mm, a diameter of 20-30 μm, and a softening temperature of 60-70°C;

[0059] The titanium aluminum alloy fiber used has an Al content of 48.3wt%, a Ti content of 49.3wt%, a Cr content of 1.8wt%, and a Mn content of 0.6wt%.

[0060] Example 1

[0061] A high-temperature, high-strength ceramic wear-resistant castable comprises the following raw materials in percentage by mass: 18% of mullite with a particle size of 8-5mm, 20% of mullite with a particle size of 5-3mm, 15% of brown corundum with a particle size of 3-1mm, 15% of brown corundum with a particle size of 1-0.074mm, 21.5% of brown corundum with a particle size ≤0.074mm, 5% of activated alumina powder, 5% of submicron SiO2 powder, 0.5% of pure calcium aluminate cement, and 1.5% of the total mass of the above raw materials of rare earth modified titanium aluminum alloy fiber, 0.1% of water reducer, 0.05% of explosion-proof fiber and 4.2% of water.

[0062] In this embodiment, the submicron SiO2 powder is obtained by mixing silicon tetrachloride and oxygen in a molar ratio of 1:6.3, burning at 2420°C for 2.6 hours, and then cooling and solidifying; its SiO2 content is 99.938wt%, Fe2O3 content is 0.0014wt%, Al2O3 content is 0.0015wt%, Na2O content is 0.014wt%, K2O content is 0.011wt%, SO3 content is 0.021wt%, and pH value is 6.9; it is spherical amorphous silicon powder with a unimodal distribution of particle size, D 10 0.13μm, D 50 0.34μm, D 90 0.81μm, D 99 It is 0.89μm.

[0063] In this embodiment, the preparation method of rare earth modified titanium aluminum alloy fiber includes the following steps:

[0064] 1) dissolving lanthanum chloride, cerium chloride and ytterbium nitrate in a solvent at a molar ratio of 2.2:2.5:1, wherein the solvent is a mixed solution of NaCl and NaNO3 with a mass concentration of 32% (the mass ratio of NaCl and NaNO3 is 1:1), to obtain a mixed rare earth solution; the total mass concentration of lanthanum chloride, cerium chloride and ytterbium nitrate in the mixed rare earth solution is 12%;

[0065] 2) placing the titanium aluminum alloy fiber into a mixed rare earth solution for vacuum impregnation, wherein the mass ratio of the titanium aluminum alloy fiber to the mixed rare earth solution is 1:2.2, the vacuum degree is 0.068 MPa, the impregnation time is 73 h, and after the impregnation is completed, the fiber is taken out and dried at 108° C. for 22 h to obtain a titanium aluminum alloy fiber after a single treatment;

[0066] 3) mixing lanthanum chloride, cerium sulfate and ytterbium chloride in a mass ratio of 2.6:1.7:1 to obtain a mixed rare earth coating material;

[0067] 4) Applying a mixed rare earth coating material on the surface of the titanium aluminum alloy fiber after the single treatment, wherein the mass ratio of the titanium aluminum alloy fiber after the single treatment to the mixed rare earth coating material is 9.6:1; drying at 108°C for 21 hours, and then heating to 359°C at a rate of 2.5°C / min and keeping warm for 3.2 hours to solidify, thereby obtaining a rare earth modified titanium aluminum alloy fiber; the rare earth modified titanium aluminum alloy fiber has a length of 40 to 50 mm, a diameter of 0.8 to 1.0 mm, and a softening temperature of 1600 to 1650°C.

[0068] Example 2

[0069] A high-temperature, high-strength ceramic wear-resistant casting material comprises the following raw materials in percentage by weight: 20% of mullite with a particle size of 8-5mm, 17% of mullite with a particle size of 5-3mm, 16% of brown corundum with a particle size of 3-1mm, 15% of brown corundum with a particle size of 1-0.074mm, 19.4% of brown corundum with a particle size of ≤0.074mm, 6% of activated alumina powder, 6% of submicron SiO2 powder, 0.6% of pure calcium aluminate cement, and 1.3% of the total weight of the above raw materials of rare earth modified titanium aluminum alloy fiber, 0.12% of water reducer, 0.06% of explosion-proof fiber and 3.9% of water.

[0070] In this embodiment, the submicron SiO2 powder is obtained by mixing silicon tetrachloride and oxygen in a molar ratio of 1:6.6, burning at 2445°C for 2.4 hours, and then cooling and solidifying; its SiO2 content is 99.941wt%, Fe2O3 content is 0.0013wt%, Al2O3 content is 0.0014wt%, Na2O content is 0.013wt%, K2O content is 0.012wt%, SO3 content is 0.022wt%, and pH value is 7.2; it is spherical amorphous silicon powder with a unimodal distribution of particle size, D 10 0.14μm, D 50 0.36μm, D 90 0.82μm, D 99 It is 0.91μm.

[0071] In this embodiment, the preparation method of rare earth modified titanium aluminum alloy fiber includes the following steps:

[0072] 1) dissolving lanthanum nitrate, cerium sulfate and ytterbium sulfate in a solvent at a molar ratio of 2.4:2.3:1, wherein the solvent is a mixed solution of NaNO3 and Na2SO4 with a mass concentration of 37% (the mass ratio of NaNO3 and Na2SO4 is 1:1), to obtain a mixed rare earth solution; the total mass concentration of lanthanum nitrate, cerium sulfate and ytterbium sulfate in the mixed rare earth solution is 14%;

[0073] 2) placing the titanium aluminum alloy fiber into a mixed rare earth solution for vacuum impregnation, wherein the mass ratio of the titanium aluminum alloy fiber to the mixed rare earth solution is 1:2.8, the vacuum degree is 0.087 MPa, the impregnation time is 71 h, and after the impregnation is completed, the fiber is taken out and dried at 107° C. for 23 h to obtain a titanium aluminum alloy fiber after a single treatment;

[0074] 3) mixing lanthanum chloride, cerium sulfate and ytterbium chloride in a mass ratio of 2.7:1.8:1 to obtain a mixed rare earth coating material;

[0075] 4) applying a mixed rare earth coating material on the surface of the titanium aluminum alloy fiber after the single treatment, wherein the mass ratio of the titanium aluminum alloy fiber after the single treatment to the mixed rare earth coating material is 9.8:1; drying at 107°C for 22 hours after applying, and then heating to 380°C at a rate of 2.6°C / min and keeping warm for 3.3 hours to solidify, thereby obtaining a rare earth modified titanium aluminum alloy fiber; the rare earth modified titanium aluminum alloy fiber has a length of 40 to 50 mm, a diameter of 0.8 to 1.0 mm, and a softening temperature of 1600 to 1650°C.

[0076] Example 3

[0077] A high-temperature, high-strength ceramic wear-resistant casting material comprises the following raw materials in percentage by weight: 15% of mullite with a particle size of 8-5mm, 18% of mullite with a particle size of 5-3mm, 18% of brown corundum with a particle size of 3-1mm, 18% of brown corundum with a particle size of 1-0.074mm, 16.6% of brown corundum with a particle size of ≤0.074mm, 7% of activated alumina powder, 7% of submicron SiO2 powder, 0.4% of pure calcium aluminate cement, and 1.1% of the total weight of the above raw materials of rare earth modified titanium aluminum alloy fiber, 0.13% of water reducer, 0.07% of explosion-proof fiber and 4.1% of water.

[0078] In this embodiment, the submicron SiO2 powder is obtained by mixing silicon tetrachloride and oxygen in a molar ratio of 1:6.4, burning at 2428°C for 2.5 hours, and then cooling and solidifying; its SiO2 content is 99.943wt%, Fe2O3 content is 0.0012wt%, Al2O3 content is 0.0022wt%, Na2O content is 0.015wt%, K2O content is 0.013wt%, SO3 content is 0.025wt%, and pH value is 7.0; it is spherical amorphous silicon powder with a unimodal distribution of particle size, D 10 0.12μm, D 50 0.33μm, D 90 0.80μm, D 99 It is 0.88μm.

[0079] In this embodiment, the preparation method of rare earth modified titanium aluminum alloy fiber includes the following steps:

[0080] 1) dissolving lanthanum chloride, cerium sulfate and ytterbium sulfate in a molar ratio of 2.1:2.6:1 in a solvent, wherein the solvent is a mixed solution of NaCl and Na2SO4 with a mass concentration of 35% (the mass ratio of NaCl and Na2SO4 is 1:1), to obtain a mixed rare earth solution; the total mass concentration of lanthanum chloride, cerium chloride and ytterbium nitrate in the mixed rare earth solution is 13%;

[0081] 2) placing the titanium aluminum alloy fiber into a mixed rare earth solution for vacuum impregnation, wherein the mass ratio of the titanium aluminum alloy fiber to the mixed rare earth solution is 1:2.6, the vacuum degree is 0.079 MPa, the impregnation time is 72 h, and after the impregnation is completed, the fiber is taken out and dried at 109° C. for 21 h to obtain a titanium aluminum alloy fiber after a single treatment;

[0082] 3) mixing lanthanum chloride, cerium sulfate and ytterbium chloride in a mass ratio of 2.9:1.6:1 to obtain a mixed rare earth coating material;

[0083] 4) Applying a mixed rare earth coating material on the surface of the titanium aluminum alloy fiber after the single treatment, wherein the mass ratio of the titanium aluminum alloy fiber after the single treatment to the mixed rare earth coating material is 9.3:1; drying at 106°C for 23 hours, and then heating to 362°C at a rate of 2.4°C / min and keeping warm for 3.4 hours to solidify, thereby obtaining a rare earth modified titanium aluminum alloy fiber; the rare earth modified titanium aluminum alloy fiber has a length of 40 to 50 mm, a diameter of 0.8 to 1.0 mm, and a softening temperature of 1600 to 1650°C.

[0084] The high temperature and high strength ceramic wear-resistant castable in the above embodiment is prepared and constructed in the following steps:

[0085] 1) After pre-mixing mullite of various particle sizes, brown corundum of various particle sizes, activated alumina powder, submicron SiO2 powder and pure calcium aluminate cement, rare earth modified titanium aluminum alloy fiber, water reducer and explosion-proof fiber are added and stirred and mixed, and finally water is added and stirred and mixed to obtain a high temperature and high strength ceramic wear-resistant castable;

[0086] 2) The high-temperature and high-strength ceramic wear-resistant material is vibrated and cast. The material is demoulded after natural hardening for 20 to 24 hours, and then wet-cured for 72 to 84 hours before baking. The baking system is: first heat to 150°C and keep warm for 36 hours, then heat to 350°C and keep warm for 24 hours, and finally heat to 650°C and keep warm for 24 hours. The above heating rates are all 10°C / h. After baking, the temperature is raised to the working temperature at a rate of 30°C / h for service.

[0087] Comparative Example 1

[0088] The difference between Comparative Example 1 and Example 1 is only that:

[0089] 1) Submicron SiO2 powder was replaced with commercially available high-purity silicon powder, with SiO2 content of 99.1wt%, Fe2O3 content of 0.0018wt%, Al2O3 content of 0.0012wt%, Na2O content of 0.012wt%, K2O content of 0.032wt%, SO3 content of 0.039wt%, and pH value of 3.9; its particle size was unimodal distribution, D 10 0.16μm, D50 0.39μm, D 90 0.91μm, D 99 0.99μm;

[0090] 2) The rare earth modified titanium aluminum alloy fiber is replaced with commercially available steel fiber with a length of 40 to 50 mm, a diameter of 0.8 to 1.0 mm, and a softening temperature of 1280 to 1320°C.

[0091] The properties of the castables of various embodiments and comparative examples were tested, and the test results are shown in the table below.

[0092] Table 1 Performance test results

[0093]

[0094]

[0095] The high-strength ceramic wear-resistant castable produced by the embodiment of the present invention has high strength and high construction efficiency. In particular, the material has good thermal shock stability and wear resistance at high temperatures, does not fall off, and has a long service life of more than 10 years.

[0096] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A high temperature and high strength ceramic wear-resistant castable, characterized in that: The invention comprises the following raw materials in percentage by weight: 14-22% of mullite with a particle size of 8-5mm, 16-24% of mullite with a particle size of 5-3mm, 13-18% of brown corundum with a particle size of 3-1mm, 12-19% of brown corundum with a particle size of 1-0.074mm, 16-25% of brown corundum with a particle size ≤0.074mm, 3-7% of activated alumina powder, 4-7% of submicron SiO2 powder, 0.3-0.6% of pure calcium aluminate cement, and 1-1.5% of the total weight of the above raw materials is added with rare earth modified titanium aluminum alloy fiber, 0.05-0.15% of water reducer, 0.03-0.1% of explosion-proof fiber and 3.5-4.5% of water.

2. The high temperature and high strength ceramic wear-resistant castable according to claim 1, characterized in that: The submicron SiO2 powder is obtained by mixing silicon tetrachloride and oxygen in a molar ratio of 1:(6-7), burning at 2400-2450°C for 2-3 hours, and then cooling and solidifying.

3. The high temperature and high strength ceramic wear-resistant castable according to claim 1, characterized in that: The submicron SiO2 powder has a SiO2 content of 99.93-99.95wt%, a Fe2O3 content of 0.001-0.002wt%, an Al2O3 content of 0.001-0.003wt%, a Na2O content of 0.01-0.02wt%, a K2O content of 0.01-0.02wt%, a SO3 content of 0.01-0.03wt%, and a pH value of 6.8-7.4; the submicron SiO2 powder is a spherical amorphous silicon powder, and its particle size is unimodal distribution, D 10 0.11~0.15μm, D 50 0.31~0.37μm, D 90 0.79~0.84μm, D 99 It is 0.86~0.92μm.

4. The high temperature and high strength ceramic wear-resistant castable according to claim 1, characterized in that: The rare earth modified titanium aluminum alloy fiber has a length of 40 to 50 mm, a diameter of 0.8 to 1.0 mm, and a softening temperature of 1600 to 1650°C.

5. The high temperature and high strength ceramic wear-resistant castable according to claim 1, characterized in that: The preparation method of the rare earth modified titanium aluminum alloy fiber comprises the following steps: 1) dissolving a lanthanum source, a cerium source and an ytterbium source in a solvent to obtain a mixed rare earth solution; 2) placing the titanium-aluminum alloy fiber into a mixed rare earth solution for vacuum impregnation, taking it out and drying it to obtain a titanium-aluminum alloy fiber after a single treatment; 3) mixing lanthanum chloride, cerium sulfate and ytterbium chloride evenly to obtain a mixed rare earth coating material; 4) A mixed rare earth coating material is applied to the surface of the titanium aluminum alloy fiber after the first treatment, and then the fiber is dried and then heated and cured to obtain a rare earth modified titanium aluminum alloy fiber.

6. The high temperature and high strength ceramic wear-resistant castable according to claim 5, characterized in that: The Al content in the titanium aluminum alloy fiber is 46.5-49.0wt%, the Ti content is 47.5-50.0wt%, the Cr content is 1.5-2.0wt%, and the Mn content is 0.3-0.8wt%; in the mixed rare earth solution, the molar ratio of the lanthanum source, the cerium source and the ytterbium source is (2-2.5):(2-3):1, and the total mass concentration of the lanthanum source, the cerium source and the ytterbium source is 10-15%; the vacuum degree of vacuum impregnation is 0.06-0.09MPa, and the impregnation time is 69-75h.

7. The high temperature and high strength ceramic wear-resistant castable according to claim 5, characterized in that: In the mixed rare earth coating material, the mass ratio of lanthanum chloride, cerium sulfate and ytterbium chloride is (2.5-3): (1.5-2): 1; the mass ratio of the titanium aluminum alloy fiber after the one-time treatment to the mixed rare earth coating material is (9-10): 1; the curing temperature of the heating curing is 350-400°C, the insulation time is 3-3.5h, and the heating rate is 2-3°C / min.

8. The high temperature and high strength ceramic wear-resistant castable according to claim 1, characterized in that: The mullite is mullite M60; the brown corundum has an Al2O3 content of 94.5-95.5wt%, a SiO2 content of 0.5-0.8wt%, a Fe2O3 content of 0.01-0.03wt%, a CaO content of 0.2-0.3wt%, a C content of 0.05-0.12wt%, a S content of 0.05-0.08wt%, and a volume density of ≥3.85g / cm 3 The Al2O3 content of the activated alumina powder is >99.5wt%, and the median particle size D 50 The pure calcium aluminate cement is CA70 calcium aluminate cement; the explosion-proof fiber is polypropylene fiber, with a length of 3 to 3.5 mm, a diameter of 20 to 30 μm, and a softening temperature of 60 to 70°C.

9. A method for preparing a high temperature and high strength ceramic wear-resistant castable according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mullite of various particle sizes, brown corundum of various particle sizes, activated alumina powder, submicron SiO2 powder and pure calcium aluminate cement are pre-mixed, and then rare earth modified titanium aluminum alloy fiber, water reducer and explosion-proof fiber are added and stirred and mixed, and finally water is added and stirred to obtain a high-temperature and high-strength ceramic wear-resistant castable.

10. A construction method for the high temperature and high strength ceramic wear-resistant castable according to any one of claims 1 to 8, characterized in that: The following steps are involved: The high-temperature and high-strength ceramic wear-resistant material is vibrated into shape and poured as a whole. After 20 to 24 hours of natural hardening, it is demoulded and then wet-cured for 72 to 84 hours before baking. The baking system is as follows: first heat to 140 to 160°C and keep warm for 32 to 40 hours, then heat to 335 to 375°C and keep warm for 20 to 26 hours, and finally heat to 620 to 680°C and keep warm for 20 to 26 hours. The above heating rates are all 10 to 12°C / h. After baking, the temperature is increased to the working temperature at a rate of 30 to 35°C / h for service.

Citation Information

Patent Citations

  • Mullite steel fiber castable

    CN101805198A

  • Zirconium-containing high-strength wear-resistant castable

    CN103382116A

  • Porous silicon carbide ceramic and preparation method thereof

    CN105294107A

  • Titanium-aluminum refractory metal part and preparation method thereof

    CN111996475A

  • Dense SiC Ceramic Products

    IE903856A1

Cited By

  • Ceramic fiber reinforced silicon carbide repairing material as well as preparation method and application thereof

    CN122444534A

  • Ceramic fiber reinforced silicon carbide repair material, its preparation method and application

    CN122444534B